BENEFITS OF HYDROLYZED COLLAGEN TYPE 1 SUPPLEMENTATION ON SKIN HEALTH - Branquinho França, Andressa; Batista dos Santos, Aparecida; Mônica dos Santos Morais, Kênia; Cardoso Morais, Gabriela (Health and Society, 2023)
Collagen is an important structural protein for the skin, and its oral supplementation has been analyzed to evaluate improvement in health parameters and prevention of skin aging. This article aims to analyze the possible benefits of type 1 hydrolyzed collagen supplementation on skin health through a systematic literature review. To collect data on the effect of type 1 collagen supplementation on the skin, a search was carried out in the Pubmed electronic database, using the following descriptors: skin, skin aging, collagen. The search resulted in 9 articles, which suggest that it is possible to obtain improvement in some parameters of the dermis, such as elasticity, wrinkles, hydration/moisture and thickness, after supplementation, in people aged 35 years and over, mainly in the female public. However, there is a divergence in the literature regarding the doses used, as well as the time of supplementation, which shows a lack of standardization in order to define what would be the best dosage and for how long the type 1 hydrolyzed collagen supplementation would be necessary. , therefore, it is recommended that further studies be carried out, using a standard dose and time.